A Scoping Review of Peer-Led Physical Activity Interventions Involving Young People: Theoretical Approaches, Intervention Rationales, and Effects. Issue 5 (July 2021) - Christensen, Julie H.; Elsborg, Peter; Melby, Paulina S.; Nielsen, Glen; Bentsen, Peter
The use of peer-to-peer approaches in health promotion interventions targeting youth seems to be a strategy with great potential. The aim of this study was to synthesize and assess the elements and conditions that contribute to the effectiveness of youth-led physical activity interventions. This was done using a scoping review addressing the following three research questions: What are the theoretical and intervention rationales behind peer-led physical activity interventions? What can be established regarding the effects of such interventions on participants and peer leaders? How can such interventions be strengthened? The review included 43 studies on the peer-to-peer approach, with youth in the role as peer leaders, in physical activity interventions. The identified studies suggest that youth peer leadership initiatives can increase physical activity for youth and children. However, the studies varied on a range of parameters and did not reveal any clear patterns of factors associated with impact.